The Politics of the Female Body: Reproductive Control and Sexual Censorship in China - Shi, Ruining (Studies in Social Science & Humanities, 2025)
This article examines how the Chinese state’s governance of reproduction and sexual expression forms a gendered mode of biopolitical control, and why the recent shift from one-child restriction to two- and three-child encouragement has not led to greater bodily autonomy for women. Using feminist legal and human-rights critique alongside Foucauldian biopolitics, the study conducts discourse analysis across laws and policy documents, curricular and health materials, and platform governance rules. The findings show that reproductive policy has changed techniques rather than logic. The state continues to determine which reproductive needs become recognised rights, aligning fertility with demographic and developmental priorities. At the same time, policy, media and administrative practice produce an “ideal woman” grounded in marriage, childbearing and care, while sexual expression is regulated through de-sexualised knowledge, platform soft control and selective punitive sanctions. The article contributes a mechanism-level account linking reproductive governance and sexual censorship and proposes a rights-centered framework for evaluating policy outcomes.